Cosmovisões em conflito : discurso cristão x discurso acadêmico na Universidade Federal de Sergipe - Costa, Douglas Lima da (2020)
The combination of faith and reason is one of the constitutive pillars of Christianity. It is no coincidence that the Catholic Church led the creation of the first university institutions in Bologna, Paris, Cambridge and Oxford, in the middle of the distant 12th century. In Brazil, the trajectory of universities followed another, more secular logic. However, the tensions surrounding the modus science x religion have not been exhausted. The dynamics of modernity called into question the linearity attributed to the process of secularization. The strength of secularized thinking has acted vehemently in legitimizing the removal of religion from public spaces, among them, the university field. In this sense, the present study aimed to identify the tensions that cover the experience of Christians in the academic environment of the Federal University of Sergipe (UFS), Campus São Cristóvão, based on the techniques of construction of empirical data - bibliographic research, field research through semistructured individual interviews and content analysis of the focus groups. The results obtained structured the construction of the analysis categories: loss of plausibility, fanaticism and religion and behaviors. Through these, it was concluded that the academic environment proves to be conflictive to these individuals, who in addition to the religious bias, establish connections between themselves and promote the dialogue between faith and reason in the academic environment.